Experimental and Numerical Investigations on Deformation of Cylindrical Shell Panels to Underwater Explosion - K. Ramajeyathilagam; C.P. Vendhan; V. Bhujanga Rao (Shock and Vibration)
Experimental and numerical investigations on cylindrical shell panels subjected to underwater explosion loading are presented. Experiments were conducted on panels of size 0.8 × 0.6 × 0.00314 m and shell rise-to-span ratios h/l = 0.0, 0.05, 0.1 , using a box model set-up under air backed conditions in a shock tank. Small charges of PEK I explosive were employed. The plastic deformation of the panels was measured for three loading conditions. Finite element analysis was carried out using the CSA/GENSA [DYNA3D] software to predict the plastic deformation for various loading conditions. The analysis included material and geometric non-linearities, with strain rate effects incorporated based on the Cowper-Symonds relation. The numerical results for plastic deformation are compared with those from experiments.